Potential Phytochemical Inhibitor from Allium cepa for the Medication of COVID-19 using In-Silico Approach - Fitriani, Ika Nur; Utami, Wiji (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2020)
Infection of extreme acute respiratory syndrome coronavirus 2 triggers Coronavirus disease 2019 (COVID-19). COVID-19 has adverse consequences on persons and is getting worse in all nations. The aim of this research is to investigate the development of in-silico approach of phytochemical inhibitor used to fight COVID-19 pathway inhibition. In medicinal plants, there are many phytochemicals, however the bioactive mechanism remains uncertain. In-silico experiments offer additional evidence to confirm the inhibition of medicinal plants. Molecular docking was used to evaluate phytoconstituents from Allium cepa as COVID-19 M-pro inhibitor, compared to remdesivir (standard drug). STITCH database used to predict the interaction network process of the most potential compound. The most potential compound was oleanolic acid. Oleanolic acid with a docking score of -9.20 kcal/mol was reported as anti-COVID-19 activity. This docking score was higher than remdesivir. Oleanolic acid interacted with GLU166, CYS44, HIS41, and THR25 via the hydrogen bond. From STITCH Database, oleanolic acid interact with CASP-9, XIAP, CASP-3 signalling pathway. Oleanolic acid from Allium cepa has been reported as a possible COVID-19 M-pro inhibitor and should be studied in future studies. The experiment indicates that phytochemical inhibitor can be helpful in the medication of COVID-19.